Operative treatment of abdominal aortic aneurysms in octogenarians. When is it too much too late? - Dean, R H (1993)
OBJECTIVE: This study evaluated the value of operation for treatment of all octogenarians with ruptured abdominal aortic aneurysms (AAA). SUMMARY BACKGROUND DATA: Elective AAA resection in octogenarians is safe, with published operative mortality rates of approximately 5%. Published operative mortality rates of ruptured AAA in this age group, however, vary from 27 to 92%. METHODS: To evaluate this question, we extracted the clinical course of the 34 octogenarians submitted to AAA resection by the authors from our total experience of 548 resections performed during the past 7 1/2 years. In this subgroup of octogenarians, 18 underwent elective AAA replacement, 5 were submitted to urgent resection of active but intact AAAs, and 11 had operations for ruptured AAAs. There were 23 males and 11 females in the group. The ages ranged from 80 to 91 years. RESULTS: Operative mortality in the patients managed electively was 5.6%. Two of the five patients (40%) submitted to operation for active yet unruptured aneurysms died in the preoperative period. Finally, 10 of the 11 patients (91%) with ruptured AAAs were operative mortalities. All of these operative mortalities in the ruptured AAA subgroup had severe hypotension preoperatively (mean systolic blood pressure: 23 mm Hg). The charges associated with the management of the ruptured AAA group averaged $84,486 (range $12,537-$199,233). CONCLUSIONS: Although elective replacement of AAA in properly selected octogenarians appears valuable to prolong worthwhile life expectancy, this experience leads us to consider observation only in the treatment of octogenarians with ruptured AAA who present with severe hemodynamic instability.